IL-1α correlates with severity of hepatitis C virus-related liver diseases - Tawfik AK (Dove Medical Press, 2018)
Ahmed Khaled Tawfik,1 Ahmed Mustafa Amin,2 Mohamed Yousef,1 Noha Mohamed El-sayd,1 Heba Elashry,1 Mahmoud Elkadeem,1 Sherief Abd-Elsalam1 1Department of Tropical Medicine and Infectious Diseases, Faculty of Medicine, Tanta University, Tanta, Egypt; 2Department of Microbiology and Immunology, Faculty of Medicine, Tanta University, Tanta, Egypt Background and aims: Immunoregulatory cytokines influence the persistence of hepatitis C virus (HCV) chronic infection and the extent of liver damage. Interleukin-1 (IL-1) plays an important role in the inflammatory process. Some studies have demonstrated that IL-1α production was impaired in patients with chronic infections of HCV, implying that IL-1α may play a role in viral clearance. The aim of this study was to evaluate the serum level of proinflammatory cytokine IL-1α in patients with chronic hepatitis C (CHC). Methods: This study was performed on 20 CHC patients with cirrhosis in (Group I), 20 CHC patients without cirrhosis in (Group II), 20 hepatocellular carcinoma (HCC) patients with positive anti-HCV in (Group III), and 10 healthy subjects as a control group. Serum levels of IL-1α were measured by enzyme-linked immunoassay technique. Results: IL-1α had the highest mean concentration in the HCC group and then in the group of CHC with cirrhosis compared to the group of CHC without cirrhosis. Also, it was higher in all studied groups than in the control group (P<0.001). Statistical analysis showed that IL-1α was positively correlated with bilirubin (P≤0.001), alanine aminotransferase (P=0.006), aspartate aminotransferase (P=0.001), and viral load (P=0.001) but it was negatively correlated with albumin (P≤0.001) and Hb (P≤0.001), and was not significantly correlated with other parameters (age, international normalized ratio, urea, creatinine, white blood cells, and platelet count). Conclusion: Serum level of IL-1α was elevated in patients with CHC and its related liver diseases (liver cirrhosis and HCC) and can be used as an important parameter of inflammatory activity and for fibrosis evaluation in patients with chronic liver disease. Keywords: HCV, interleukin-1α, cirrhosis, hepatocellular carcinoma, fibrosis